UNEXPECTED SUDDEN DEATH IN A YOUNG MAN WITH MYOPERICARDITIS- A CASE REPORT - Hussain, Rafaqat; Halmai, Laszlo; Subkovas, Eduardas (Journal of Ayub Medical College Abbottabad, 2015)
A 31 years man was referred by general practitioner (GP) with chest pain preceded by sore throat a week ago. Electrocardiogram was suggestive of pericarditis and Troponin and inflammatory markers were elevated. Echocardiogram showed small pericardial effusion with normal biventricular size and function, and no regional wall motion abnormalities (RWMA). A clinical diagnosis of myopericarditis was made. Patient was in good clinical condition so he self-discharged before cardiac MRI. Two days later he died of cardiac arrest. His post mortem confirmed the diagnosis of myopericarditis. He died despite of absence of known poor prognostic features of Myopericarditis. Keywords: Myocarditis, Sudden Death, Post Mortem